PROFIL PEREMPUAN PEKERJA KEBERSIHAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Putra, Ade; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The family is the smallest community unit consisting of father, mother, and children are interdependent with each other. As one of the husband's family members are required to be able to support his entire family, but with the changing times and low forward husband education, wife is also required to play an active role in improving the economy of the family is one done by the mothers who work as female sanitary worker in the Faculty of Social and Political Sciences, University of Riau. The main reason they work is to improve the economy of the family, that wants to help her husband in making a living because of the low income so that husbands with wives participation in making a living can improve the economics of the family. The problem in this research is: 1) How socio-economic characteristics of the lives of cleaning service employed in Fisip? 2) How does the system work in the sanitation cleaning service Fisip? 3) How is the strategy cleaning service women in increasing the family income?The purpose of this study was to determine the socio-economic characteristics of cleaning service working life in Fisip UR. To find out how to work the system cleaning service hygiene in Fisip UR. And to know the strategies cleaning service in increasing the family income. Subjects in this study were female worker hygiene Faculty of Social and Political Sciences, University of Riau, amounting to 9 workers. The approach used in this study is a qualitative descriptive study. The process of collecting data using interviews, observation, and documentation. The technique used in taking the subject is by taking the overall cleanliness of the working women of the Faculty of Social and Political Science as a whole.Suggestions that the authors of this study is to convey to officials involved in the maintenance of cleanliness Fisip to give more attention to cleaning service employed CV hygiene especially in improving their welfare, and better control of the workers, especially cleaning service women in Fisip hygiene in working order Fisip hygiene is maintained and manicured clean.Keywords: Cleaning Service Women, Faculty of Social and PoliticalSciences, University of Riau